(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Elastomeric materials, both natural rubber and synthetic, are widely used in industry and civil engineering, due to their unique properties: high elasticity, low volume compressibility, capability to absorb and dissipate input energy, a linear relationship between stress and strain up to strain of 15% ÷ 20%, resistance to aggressive environmental factors. Different kind of compensation devices, vibration dampers, shock absorbers are fabricated from rubber materials.At the same time the elastomeric materials nonreversible change their properties over time, this disadvantage is called ageing.In given paper the results of experimental studying of the influence of aging on the physical-and-mechanical properties of polyurethane rubber is presented. The samples of cylindrical form were prepared from soft flexible polyurethane rubber Xenias PX30 and subjected to the artificial ageing. Accelerated aging of samples was fulfilled in accordance with European standard ISO 188:2011 (Rubber, vulcanized or thermoplastic - Accelerated ageing and heat resistance tests).The changing of volume, Shore A hardness, elastic rebound coefficient and static elasticity modulus under compression were investigated. Experiments showed the volume decrease, hardness shore increasing, elastic rebound increase and compression modulus under static loading increasing. This data are necessary for correct designing of the compensation devices to provide their working properties during all service life.